Benin : Teachers 2012 - World Bank (Washington, DC, 2015)
Achieving the right teacher policies to ensure that every classroom has a motivated, supported, and competent teacher remains a challenge, because evidence on the impacts of many teacher policies remains insufficient and scattered. Systems approach for better education results (SABER) - teachers, aims to help fill this gap by collecting, analyzing, synthesizing, and disseminating comprehensive information on teacher policies in primary and secondary education systems around the world. SABER - teachers' collects data on ten core teacher policy areas to offer a comprehensive descriptive overview of the teacher policies that are in place in each participating education system. SABER - teachers analyzes the teacher policy data collected to assess each education system's progress in achieving eight teacher policy goals: (1) setting clear expectations for teachers; (2) attracting the best into teaching; (3) preparing teachers with useful training and experience; (4) matching teachers' skills with students' needs; (5) leading teachers with strong principals; (6) monitoring teaching and learning; (7) supporting teachers to improve instruction; and (8) motivating teachers to perform. By classifying countries according to their performance on each of the eight teacher policy goals, SABER - teachers can help diagnose the key challenges that countries face in ensuring they have effective teachers. The main focus of SABER - teachers is on policy design, rather than on policy implementation. It describes Benin's performance in each of the eight teacher policy goals, alongside comparative information from education systems that have consistently scored high results in international student achievement tests and have participated in SABER - teachers.